Embolization and radiosurgery for arteriovenous malformations - Plasencia, Andres R. (Medknow Publications & Media Pvt Ltd, 2012)
The treatment of arteriovenous malformations (AVMs) requires a multidisciplinary management including microsurgery, endovascular embolization, and stereotactic radiosurgery (SRS). This article reviews the recent advancements in the multimodality treatment of patients with AVMs using endovascular neurosurgery and SRS. We describe the natural history of AVMs and the role of endovascular and radiosurgical treatment as well as their interplay in the management of these complex vascular lesions. Also, we present some representative cases treated at our institution.